The Philippine graphic/fiction awards prose anthology - Gaiman, Neil (Makati Sketchbooks, Inc., 2010)
Two archangels meet at an ice cream stand outside the Vatican to discuss plans of a righteous assassination. A powerful spacecraft, fuelled by Kris Aquino's limitless gossip, is sent to an asteroid on a mission to save the world. A man with an appetite for spoken words discovers he is not the only one with peculiar cravings and meets his match. A corpse, unaware of its sudden demise, returns to his home to the surprise and horror of his grief-stricken family and nosy neighbors. A man bound by an extraordinary gift lives a guarded life and becomes a bystander throughout his years. A domestic helper, declared a Super Maid by her nation's President, is jarred by questions of a life that could have been. These fragments torn from daydreams and nightmares compose the masterful prose and rich art of the Philippine Graphic/Fiction Awards Anthology. As a creative venture of Fully Booked and globally renowned author Neil Gaiman, the competition called upon writers and artists all over the Philippines to take up Gaiman's challenge to encourage "Filipino Unrealism." The directive was simple: keep it unreal. With a foreword written by Neil Gaiman, this compendium features the winners and short-listed entries of the prose category. Highly engaging, thought provoking and many times flavored with the unique Pinoy sense of humor, these stories are testament to the deep wellspring of Filipino talent and imagination.
A compilation of winning short stories by Filipino authors.
Keywords: Short stories, Philippine (English).; Authors, Filipino -- Fiction